Twenty priorities for future social-ecological research on climate resilience. (30th September 2020) - Beauchamp, Emilie; Hirons, Mark; Brown, Katrina; Milner-Gulland, EJ
Abstract: Faced with the global climate crisis and the inevitability of future climate shocks, enhancing social-ecological resilience has become an urgent area for research and policy internationally. Research to better understand the impacts of, and response to, climate shocks is critical to improve the resilience and well-being of affected people and places. This paper builds on the findings of a focus collection on this topic to provide a concluding and forward-looking perspective on the future of social-ecological research on climate resilience. Drawing on an expert workshop to identify research gaps, we distinguish 20 priorities for future research on climate resilience. These span four key themes: Systems and Scales, Governance and Knowledge, Climate Resilience and Development, and Sectoral Concerns. Given the need and urgency for evidence-based policies to address the climate crisis, the analysis considers the importance of understanding how findings on social-ecological resilience are used in policy, rather than solely focusing on how it is generated. Many of the priorities emphasise the governance systems within which climate research is produced, understood and used. We further reflect on the state of current evidence generation processes, emphasising that the involvement of a wider range of voices in the design, implementation and dissemination of climate resilience research is critical to developing the efficient and fair interventions it is meant to support.